2010
DOI: 10.1515/bc.2010.141
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid retention and activation of endogenous hepatic farnesoid-X-receptor in the pathogenesis of fatty liver disease in ob/ob-mice

Abstract: The nuclear bile acid receptor FXR (farnesoid-X-receptor) has recently been implicated in the pathophysiology of nonalcoholic fatty liver disease because selective FXR-agonists improve glucose and lipid metabolism in rodent models of obesity. However, the regulation of FXR and other relevant nuclear receptors as well as their lipogenic target genes in fatty liver is still not revealed in detail. Livers were harvested from 14-week-old male ob/ob mice and wild-type controls. Serum bile acids were quantified by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 51 publications
4
36
0
Order By: Relevance
“…In accordance with these data from systemic Fxr −/−, the same increase in Cyp7a1 expression in combination with decreased Bsep can be observed in ΔL Fxr mice in the present study. In this context, bile acid retention due to reduced bile acid transporter expression as observed in various rodent models of fatty liver (19,20) (25). In accordance with previous data SHP is not induced in 1% cholesterol diet animals since it has been shown that SHP induction is repressed by free fatty acids (FFA) in NAFLD patients and hepatoma cells (28).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In accordance with these data from systemic Fxr −/−, the same increase in Cyp7a1 expression in combination with decreased Bsep can be observed in ΔL Fxr mice in the present study. In this context, bile acid retention due to reduced bile acid transporter expression as observed in various rodent models of fatty liver (19,20) (25). In accordance with previous data SHP is not induced in 1% cholesterol diet animals since it has been shown that SHP induction is repressed by free fatty acids (FFA) in NAFLD patients and hepatoma cells (28).…”
Section: Discussionsupporting
confidence: 81%
“…In this regard, it is also unclear whether bile acid retention and subsequent hepatic FXR activation in fatty livers represents a causal event in the pathogenesis or rather an attempt of adaptation (19,20). Following these pertinent questions we studied organspecific liver (ΔL) and intestinal (ΔIE) Fxr knockout mice under a 1% cholesterol diet.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody staining and immune complexes detection were performed as previously described. 17 Primary antibodies used in the study were directed against basolateral Na + -dependent taurocholate cotransporting polypeptide (mNTCP 18 ), multidrug-resistance-associated protein 2 (mMRP2 19 ), bile salt export pump (BSEP 20 ), multidrug-resistance-associated protein 4 (mMRP4) (ab45602), and multidrug-resistance-associated protein 3 (mMRP3) (ab3375). Na/K-ATPase (ab7671-50) was used as a loading control.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…As a result, it can induce the lipid peroxidation and, finally, hepatic lipid accumulation. Martin and his colleagues [20] transplanted infant intestinal flora into the gut of germ-free mice and found that conjugated bile acid in terminal ileum increased and plasma lipoprotein decreased, but hepatic triglyceride increased at the same time. They inferred that the alteration of gut flora can promote the bile acid enterohepatic circulation, inhibit the synthetizing and secretion of VLDL and LDL, and result in the hepatic steatosis at last [21].…”
Section: Gut Chemical Barrier and Nafldmentioning
confidence: 99%